PENGARUH PERSEPSI DAN KEPERCAYAAN KONSUMEN TERHADAP KEPUTUSAN PENGGUNAAN E-MONEY DI TOKO PERLENGKAPAN RUMAH TANGGA MASBAGIK TIMUR - Maolida, Mita; Fatana Suastrini (Yayasan Nusantara Hasana Berdikari, 2024)
This research aims to find out (1) whether perceptions influence the decision to use e-money. (2) does consumer trust influence the decision to use e-money? (3) do consumers' perceptions and beliefs have a positive and significant effect on the decision to use e-money at East Masbagik household goods stores. This research uses quantitative methods. The population in this study are consumers who make transactions at East Masbagik household goods stores and the sample for this study as many as 90 respondents. The instrument used in this research was a questionnaire with 24 statements and the research data sources came from interviews and questionnaires. Data testing uses multiple linear regression. The research results show a perception with a significant value of 0.000 < 0.05 and a calculated value of 5.045 > from t table 1.987. This shows that the perception variable has a significant influence on the decision to use e-money. The significant value of consumer trust is 0.000 <0.05 and the t-batung value is 8.185. This shows that the consumer trust variable has a significant influence on the decision to use e-money. With the coefficient of determination (R²) obtained at 0.687% and 32% due to other variables. The results of this research indicate that the perception variable X; and consumer trust X: has a positive and significant effect on the decision to use e-money.